Vprašanje fikcije - Vrdlovec, Zdenko (Monitor ISH, 2008)
After introducing the concepts of mimesis, mimetism, and feigning, the article concentrates on a pragmatic approach to the question of fiction, claiming that fictional representations are characterised not so much by their logical status as by their use. Fiction is "beyond true and false", suspending the questions of the referential value and ontological status of its representations. In fictional worlds, the principle of verification is replaced by the principle of intrinsic coherence. Entering a fictional world, we do not ask about its referentiality in the logical sense. Instead of inquiring into the relation of fiction to reality, we must ask what kind of reality fiction is in its own right, and how it functions in the reality of our lives.
Keywords: fiction; fikcija; reality; resničnost; reprezentacija; mimesis